Electronic Academic Report (e-AR) - Tutiyana Mohamed; Shirley Arvilla Andrew; Diana Indim (Malaysia Journal of Invention and Innovation, 2024)
Students' academic performance is reported in a program or faculty meeting by the lecturer teaching their respective course code to be recorded and acted upon by the academic advisor every semester. All lecturers must be present to report their student's academic performance on the course code taught during the meeting. If the lecturer cannot attend the meeting, the student's academic performance report cannot be recorded, and the academic advisor unaware of the students who need attention. Sometimes, some lecturers did not have time to prepare the report, and some information was missing. In addition, the secretary finds it challenging to record the names of students with problems with the correct spelling of names if more than one since the previous reporting was manually reported without any template that served as guidance to the lecturers. Based on the weaknesses identified, an academic report application (e-AR) was adopted to improve from a template to an electronic application. e-AR makes it easier for the secretary to take notes, for the lecturers to make a report, and for the academic advisors to identify the students who need attention. e-AR is a digital tool designed for reporting and monitoring students' performance in all courses throughout the semester. Lecturers can quickly fill out the e-AR and click submit the report to the program coordinator in real time. This application facilitates academic reporting and thorough monitoring of all course codes in the current semester. e-AR helps the lecturer identify the potentially high failure course code, the problem faced by the student, and the improvement measures, which will guide the student's academic performance and help them graduate on time.